1999
DOI: 10.1097/00004872-199917100-00004
|View full text |Cite
|
Sign up to set email alerts
|

A randomized trial on effects of hormone therapy on ambulatory blood pressure and lipoprotein levels in women with coronary artery disease

Abstract: One year of HRT in patients with CAD does not influence ABP. Oral HRT induces beneficial effects on lipoprotein levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
23
0
3

Year Published

2001
2001
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 37 publications
3
23
0
3
Order By: Relevance
“…However, in the present study, estrogen therapy did not alter blood pressure, MSNA, blood flow, or vascular resistance. Nevertheless, our results are in accordance with those of other studies (57,60,66,68). The discrepancies might be explained by differences in the type or dose of estrogen administered.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, in the present study, estrogen therapy did not alter blood pressure, MSNA, blood flow, or vascular resistance. Nevertheless, our results are in accordance with those of other studies (57,60,66,68). The discrepancies might be explained by differences in the type or dose of estrogen administered.…”
Section: Discussionsupporting
confidence: 90%
“…Among previously normotensive women treated with hormone replacement therapy, blood pressure has been shown to decrease (4,5), increase (67,70), and be unaffected (57,60,66). Similarly, studies have shown hormone replacement therapy to reduce heart rate (HR) significantly (31,68), whereas others have shown that it has no effect on HR (51,68).…”
mentioning
confidence: 99%
“…The current study used a double-blind, randomised, placebocontrolled design with adequate power to detect small changes in clinic and ambulatory blood pressure produced by different doses of a C21 progestogen administered in a cyclical regimen in doses spanning the usual clinical dose range combined with a fixed daily dose of oral oestrogen. The results of the current study are consistent with those of previous studies, including the PEPI study, which have found no change [2][3][4][5][6][7][8][9][10]12 or a reduction [24][25][26]29 in blood pressure associated with the addition of a progestogen to 'replacement' doses of oestrogen.…”
Section: Discussionsupporting
confidence: 91%
“…In women over the age of 60, show gradual increases of blood pressure over a period of 5 to 20 years, until hypertension is highly prevalent in women as in men. Estrogen reduction after menopause is partially responsible for this effect and experimental data indicate that the change in the estrogen/androgen ratio seems to be the cause (Akkad et al, 1997;Pripp et al, 1999). Epidemiological studies show that androgens are important determinants of sex differences in blood pressure.…”
Section: Role Of Androgens In Hypertensionmentioning
confidence: 99%